A pressure sensor based on a nitride membrane using single-crystalline piezoresistors - Folkmer, Bernd; Steiner, Peter; Lang, Walter (Sensors and actuators. A. Physical., 1996)
The realization of a piezoresistive pressure sensor, applying a process that combines the advantages of silicon nitride membranes with those of monocrystalline silicon transducers, is presented. This technology, which leads to small devices, low spread in sensor performance and moderate process cost, can be utilized for mechanical transducers, e.g., pressure sensors, accelerometers, etc., as well as for thermal sensor devices. The design, technology and characterization of a 500 mbar pressure sensor are described.